The Montreal model: an integrative biomedical-psychedelic approach to ketamine for severe treatment-resistant depression - Garel, Nicolas; Drury, Jessica; Thibault Lévesque, Julien; Goyette, Nathalie; Lehmann, Alexandre; Looper, Karl; Erritzoe, David; Dames, Shannon; Turecki, Gustavo; Rej, Soham; Richard-Devantoy, Stephane; Greenway, Kyle T. (Frontiers in Psychiatry, 2023)
Background: Subanesthetic ketamine has accumulated meta-analytic evidence for rapid antidepressant effects in Treatment-Resistant Depression (TRD), resulting in both excitement and debate. Many unanswered questions surround ketamine's mechanisms of action and its integration into real-world psychiatric care, resulting in diverse utilizations that variously resemble electroconvulsive therapy, conventional antidepressants, or serotonergic psychedelics. There is thus an unmet need for clinical approaches to ketamine that are tailored to its unique therapeutic properties.Methods: This article presents the Montreal Model, a comprehensive biopsychosocial approach to ketamine for severe TRD refined over six years in public healthcare settings. To contextualize its development, we review the evidence for ketamine as a biomedical and as a psychedelic treatment of depression, emphasizing each perspectives' strengths, weaknesses, and distinct methods of utilization. We then describe the key clinical experiences and research findings that shaped the model's various components, which are presented in detail.Results: The Montreal Model, as implemented in a recent randomized clinical trial, aims to synergistically pair ketamine infusions with conventional and psychedelic biopsychosocial care. Ketamine is broadly conceptualized as a brief intervention that can produce windows of opportunity for enhanced psychiatric care, as well as powerful occasions for psychological growth. The model combines structured psychiatric care and concomitant psychotherapy with six ketamine infusions, administered with psychedelic-inspired nonpharmacological adjuncts including rolling preparative and integrative psychological support.Discussion: Our integrative model aims to bridge the biomedical-psychedelic divide to offer a feasible, flexible, and standardized approach to ketamine for TRD. Our learnings from developing and implementing this psychedelic-inspired model for severe, real-world patients in two academic hospitals may offer valuable insights for the ongoing roll-out of a range of psychedelic therapies. Further research is needed to assess the Montreal Model's effectiveness and hypothesized psychological mechanisms.